Do you look longer at attractive faces? It depends on what you are looking for - Dirk Kerzel; Nicolas Prigoda; Olivier Renaud (i-Perception)
Evolutionary psychology suggests that we are attuned to relevant information in the environment. For example, attention may be attracted by physical beauty because it is important for finding a partner with good reproductive health. Consistently, previous studies found that attention stayed longer on attractive than unattractive faces. We asked whether this tendency was automatic and varied participants’ implicit search intentions to be either consistent or inconsistent with the presumably automatic tendency to attend to attractive faces. To create an implicit intention to look at attractive faces, participants searched for a happy face in an array of neutral faces because happy faces are rated as more attractive than neutral faces. To create the opposite intention to look at unattractive faces, participants searched for a disgusted or sad face because disgusted or sad faces are rated as less attractive than neutral faces. We found longer fixation durations on attractive faces when participants searched for happy faces. When participants searched for disgusted or sad faces, however, fixation durations were longer on unattractive faces. Thus, the search task determined whether attractive faces were looked at longer. The tendency to attend to attractive faces is therefore not automatic but can be overruled by search intentions.